Relationship between obstructive sleep apnea-specific symptoms and cardiac function before and after adenotonsillectomy in children with adenotonsillar hypertrophy - ÇİNÇİN, AHMET ALTUĞ (ELSEVIER IRELAND LTD, 2014)
Objective: The aim of our study was to investigate subclinical cardiac disturbances in patients with symptoms due to adenotonsillar hypertrophy (ATH) and the impact of adenotonsillectomy (AT) using conventional and novel echocardiographic measures. Material and methods: Thirty patients with grade 3 or 4 ATH (mean age: 7.86 +/- 3.83 years; 10 females) and 30 healthy, age- and sex-matched volunteers (mean age, 8 +/- 2.77; 14 females) were enrolled in the study. In addition to conventional two-dimensional and Doppler echocardiographic parameters, tissue Doppler parameters, including myocardial performance indices (MPIs) of both the right (RV) and left ventricle (LV), were studied. The severity of obstructive sleep apnea (OSA) was determined using the OSA-18 health quality questionnaire. The OSA-18 questionnaire and echocardiographic examination were repeated after AT in patients with ATH. Results: The total OSA-18 scores for the control, preoperative, and postoperative groups were 39.56 +/- 19.98, 80.63 +/- 22.32, and 44.10 +/- 20.31, respectively. Conventional parameters were not different among the groups. The mean pulmonary artery pressure estimated using the Mahan formula was increased in the ATH group compared with that in the control group (21.72 +/- 4.25 vs. 12.43 +/- 3.83, respectively; p <0.001) and significantly improved after AT (21.72 +/- 4.25 vs. 16.09 +/- 4.53; p <0.001). The RV MPI was significantly different between the control and ATH groups (0322 +/- 0.052 vs. 0.383 +/- 0.079, respectively; p = 0.001). Both the LV and RV MPI significantly improved (0.515 +/- 0.066 vs. 0.434 +/- 0.052, p <0.001; and 0.383 +/- 0.079 vs. 0.316 +/- 0.058, p = 0.018, respectively) after surgery for ATH. Conclusions: Our study revealed that the patients with OSA-specific symptoms due to ATH had higher pulmonary artery pressure and impaired RV function according to novel echocardiographic parameters. Surgery for ATH seems to have an important effect on both LV and RV function. (C) 2014 Elsevier Ireland Ltd. All rights reserved.
Keywords: Obstructive sleep apnea; Adenotonsillectomy; Cardiac function; Sleep; Echocardiography; RIGHT-VENTRICULAR FUNCTION; QUALITY-OF-LIFE; MYOCARDIAL PERFORMANCE INDEX; PULMONARY-ARTERY PRESSURE; TISSUE DOPPLER; ECHOCARDIOGRAPHIC-ASSESSMENT; TEI INDEX; HYPERTENSION; DISEASE; HEART